2017
DOI: 10.1111/opo.12380
|View full text |Cite
|
Sign up to set email alerts
|

Change in over‐refraction after scleral lens settling on average corneas

Abstract: Despite a significant change in the central corneal clearance due to thinning of the fluid reservoir as the scleral lens settled (an average decrease of 83 μm after wearing the lenses for 6-8 h), there was not a statistically significant change in the subjective over-refraction (sphere, cylinder, and axis) or best sphere or visual acuity. This study has confirmed that there is no link between reduction in central corneal clearance and change in over-refraction for average corneas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 5 publications
2
16
0
Order By: Relevance
“…The use of a relatively small, homogenous sample of participants with healthy eyes is also a limitation since the results cannot be generalised to contact lens wearers with abnormal corneae, or different lens designs. However, our data is in broad agreement with the trends described in previously published settling and decentration data from both normal [15,17,20,32] and keratoconic patients [14,18,22,35] wearing a variety of scleral lenses.…”
Section: Discussionsupporting
confidence: 93%
“…The use of a relatively small, homogenous sample of participants with healthy eyes is also a limitation since the results cannot be generalised to contact lens wearers with abnormal corneae, or different lens designs. However, our data is in broad agreement with the trends described in previously published settling and decentration data from both normal [15,17,20,32] and keratoconic patients [14,18,22,35] wearing a variety of scleral lenses.…”
Section: Discussionsupporting
confidence: 93%
“…reported that lower initial central corneal clearance was associated with less horizontal miniscleral lens decentration. The mean change in central corneal clearance after 5 h of lens wear (−70 ± 20 μm) was similar to previous studies using miniscleral lenses of similar diameter …”
Section: Discussionsupporting
confidence: 89%
“…Figure displays the mean change in central corneal clearance over an eight hour period for five different scleral lens designs, presented as the percentage reduction in the initial clearance since larger diameter lenses (with greater sagittal depths) typically provide a greater initial corneal vault . The viscosity of the fluid used to fill the scleral bowl does not appear to impact lens settling in the short term and while the reduction in the post‐lens tear layer thickness over the course of the day does influence the optics of the combined contact lens–tear layer system, the effect is minimal (about a 0.25 D myopic shift in eyes with flat or normal corneal curvature) . However, this change in optical power is more pronounced for thicker post‐lens tear layers, steeper corneae, steeper lens fits and higher plus powers.…”
Section: Assessing the Fit Of Scleral Contact Lensesmentioning
confidence: 99%